On Emotions and Decisions. Issue 8 (September 2016) - Creo, Robert A.
Abstract : Last month, Master Mediator columnist Bob Creo looked at the role of emotions in conflict resolution decision making. In Part 2 this month, he factors in the effects of shame and guilt .